Single-organ sarcoidosis involving hepatic, lacrimal, and Cardiac - B N Shiva Prasad; Ravi Puranik; Venugopal Anandaswamy; P Jayakumar (Indian Journal of Rheumatology)
Sarcoidosis is a multisystem idiopathic granulomatous disease. Lung is the most common organ involved but can involve any organ. The skin, eyes, joints, and heart are affected in a significant fraction of patients. Extrapulmonary sarcoidosis may be the major manifestation of the disease. Extrapulmonary disease may manifest before, concurrent with, or after the development of pulmonary disease or as isolated independent disease. We present three cases of isolated organ sarcoidosis involving the liver, lacrimal, and heart. Isolated organ involvement is difficult to diagnose and the treatment of Isolated organ is not defined.